Teaching english for specific purposes (ESP) - Sharapova, V. V.; Kiselyova, T. V.; Smyhliakova, M. K. (My University, 2017)
The main aspects of ESP teaching have been observed. This article highlights that in ESP it is a needs analysis that determines which language skills are most needed by the students, and the syllabus is designed accordingly. It also points out that the most important aspect lies in the learners and their purposes for learning English in order to communicate and have a set of professional skills and to perform particular job-related functions.
Sharapova, V. V. Teaching english for specific purposes (ESP). Teaching strategies / V. V. Sharapova, T. V. Kiselyova, M. K. Smyhliakova // Гуманіт. вісн. НУК. – Миколаїв : НУК, 2017. – Вип. 10. – С. 22–24.
Keywords: English for specific purposes (ESP); skills; ESP Curriculum; language proficiency